Mango (Mangifera indica cv. Azúcar) antiinflammatory and chemopreventive role during colorectal carcinogenesis (2016)
ABSTRACT: Chemopreventive activities of natural compounds result in the modulation of several pathways and molecular targets. It is common to find effective potential candidates for cancer chemoprevention with anti-inflammatory properties. Mango (Mangifera indica cv. Azúcar) has shown anticarcinogenic effects and it is a source of bioactive compounds. This study evaluated the effects of mango on Aberrant Crypt Foci formation and inflammatory biomarkers after initiation of colon carcinogenesis in AOM-treated mice. Ripped mango pulp (Mangifera indica cv. Azúcar) composition was identified by HPLC. Azoxymethane-treated mice received the fruit (0.3% w/v) for eight weeks and the distal part of colon was collected and stained with methylene blue to look for aberrant crypt foci (ACF); scrapped mucosal cells were processed for prostaglandin E2 detection by ELISA; and blood levels of pro-inflammatory cytokines (interleukin-1Beta, tumor necrosis factor-alpha, interleukin 6) were also assessed by ELISA. Student’s t.test was used for the comparisons between mango treated and untreated groups. ACF formation was reduced by 67.5% and prostaglandin E2 levels were also reduced in mice which ingested the fruit. Cytokines levels were unchanged by mango consumption. In the chromatography were identified phenolic acids and Beta-carotene. Mango pulp showed chemopreventive effects through the reduction of ACF formation, by means of blocking hyperproliferation which is correlated with decreasing levels of PGE2.